Enhanced intentional controlled islanding with BESS integration - Amar Saufi Nasir; Nur Zawani Saharuddin; Izham Zainal Abidin; Ezreen Farina Shair; Sharin Ab Ghani (Institute of Advanced Engineering and Science, 2026)
Severe power system outages can lead to uncontrolled failures and system instability. Intentional controlled islanding is a strategy that deliberately splits the power system into balanced, stand-alone islands to ensure continuous electricity supply until full restoration. However, the execution of islanding may result in certain islands being unbalanced in terms of generation and load. In such cases, load shedding is implemented to achieve balanced stand-alone islands. Nevertheless, load shedding is not the best option as it will result in more users experiencing power disruptions. Therefore, this study explores the integration of battery energy storage systems (BESS) to enhance intentional controlled islanding, with the aim to form balance islands without the need to execute load shedding. This study evaluates the effectiveness of BESS in forming balanced islands and optimizing islanding strategies. The IEEE 30-bus and IEEE 118-bus test systems were used to validate the effectiveness of BESS in enhancing the intentional controlled islanding implementation. The results demonstrated the role of BESS in facilitating intentional controlled islanding, forming stable and balanced island operations without the need for a load shedding scheme. These findings highlight the potential of BESS to enhance the reliability and effectiveness of intentional controlled islanding.